Using Movie in Teaching Writing (A Classroom Action Research) - Masruddin Masruddin (Ethical Lingua: Journal of Language Teaching and Literature, 2015)
This is a classroom action research which is focused on improving students’ ability in writing a narrative paragraph by using short movie. Before doing the research, the researcher found that most of the students are still low ability in writing; they cannot decide what they are going to write. In doing the research, I asked the students watched the English movie then I asked them to write paragraph in English, then I asked to do peer evaluation, then finally we came to the discussion part. We discussed about the errors that they found in the peer evaluation process. Then, I gave suggestions and the correct way in writing paragraph to the students. This study was done in three cycles. In the first cycle, the researcher still found some weaknesses, then we tried to make some solutions, then we did the second cycle but we still found some problems especially about the students’ participation, then we discussed again, finally at the third cycle we got good result in students’ participation and also students’ writing were satisfied. The result of the research was that the students’ ability in writing paragraph in English improved. Also they enjoy learning English writing by watching English movie.